2021
DOI: 10.33009/fsop_jpss127933
|View full text |Cite
|
Sign up to set email alerts
|

Learning How to Tailor Programmatic Offerings to Support Low-income, First-generation, and Racially Minoritized Student Success

Abstract: This study focused on the process of how the staff at the Thompson Scholars Learning Community (TSLC), a comprehensive college transition program, tailored the programmatic offerings to meet the needs of low-income, first generation and racialized minority students. Because college students are complex individuals, each of whom faces a unique set of challenges and opportunities, it is reasonable to hypothesize that tailoring support services to the multiple needs of each student may make them more effective. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The reflective process used both formal and informal data to inform decision-making. As a result of this reflective practice, the staff and faculty often made adjustments to tailor the program to fit the specific needs of racialized minorities, first-generation students, or commuter and working students, for example 6 (Kezar et al, 2021).…”
Section: Presentation Of Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The reflective process used both formal and informal data to inform decision-making. As a result of this reflective practice, the staff and faculty often made adjustments to tailor the program to fit the specific needs of racialized minorities, first-generation students, or commuter and working students, for example 6 (Kezar et al, 2021).…”
Section: Presentation Of Datamentioning
confidence: 99%
“…Our study also expands on the CECE model's attention to being identity-conscious. Our study identified a process called tailoring (see Kezar et al, 2020Kezar et al, , 2021 that modifies interventions and support based on specific student needs, often related to their identities and cultural background, but are broader than this and also entail their experiences and situations such as working, commuting, family responsibilities among other issues that are addressed through the tailoring process. The tailoring process is similar to case management where students' multiple identities and needs are assessed and addressed.…”
Section: Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Career centers and offices providing related services should conduct outreach targeted to FGCSs, perhaps through mailers to also help families learn about services. As institutions build these services, there may be an opportunity to use individual advising and counseling services to help students identify their unique journeys, desires, and their educational success, as well as build group-level services tailored to FGCSs, creating a community of students with shared experiences (see Kezar et al, 2021). FGCSs comprise a significant share of students in higher education today, and ensuring that they have the tools to succeed, both in college and beyond, is critical to the operation and success of U.S. postsecondary systems.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%